Alcohol and atherosclerosis - DA LUZ,PROTASIO L. (2001)
Atherosclerosis is manifested as coronary artery disease (CAD), ischemic stroke and peripheral vascular disease. Moderate alcohol consumption has been associated with reduction of CAD complications. Apparently, red wine offers more benefits than any other kind of drinks, probably due to flavonoids. Alcohol alters lipoproteins and the coagulation system. The flavonoids induce vascular relaxation by mechanisms that are both dependent and independent of nitric oxide, inhibits many of the cellular reactions associated with atherosclerosis and inflammation, such as endothelial expression of vascular adhesion molecules and release of cytokines from polymorphonuclear leukocytes. Hypertension is also influenced by the alcohol intake. Thus, heavy alcohol intake is almost always associated with systemic hypertension, and hence shall be avoided. In individuals that ingest excess alcohol, there is higher risk of coronary occlusion, arrhythmias, hepatic cirrhosis, upper gastrointestinal cancers, fetal alcohol syndrome, murders, sex crimes, traffic and industrial accidents, robberies, and psychosis. Alcohol is no treatment for atherosclerosis; but it doesn't need to be prohibited for everyone. Thus moderate amounts of alcohol (1-2 drinks/day), especially red wine, may be allowed for those at risk for atherosclerosis complications.